Hubungan Minat, Lari 30 Meter Dan Daya Ledak Otot Tungkai Dengan Kemampuan Lompat Jauh - Cahyadi, Agung; Mirza; Hidayat, Rahmad; Arkan, Muhammad (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Physical education learning is influenced by physiological and psychological factors. In Athletics material, especially Long Jump sub-material, physiological factors are physical conditions in this case are 30 Meter Run and leg muscle explosive power while psychological factors include Interest aspects. The Long Jump Ability of Students of SMA Negeri 1 Peulimbang in the 2012/2013 Academic Year is relatively poor, this is illustrated by the average value, this is illustrated by the data on the results of long jump learning of students at the school which is still below average. These poor results are inseparable from the physiological and psychological factors that influence it. This study aims to determine the relationship between Interest (X1), 30 Meter Run (X2) and Leg Muscle Explosive Power (X3) with Long Jump Ability (Y) of Students of SMA Negeri 1 Peulimbang in the 2012/2013 Academic Year. This type of research is descriptive correlational research, namely describing the relationship between the variables studied. The number of samples in this study was 34 Students of SMA Negeri 1 Peulimbang in the 2012/2013 Academic Year. From the results of the research data analysis, the following results were obtained; there is a relationship between X1 and Y with a correlation coefficient of 0.59. There is a relationship between X2 and Y with a correlation coefficient of 0.39. There is a relationship between X3 and Y with a correlation coefficient of 0.50. The correlation coefficient together X1, X2, X3 with Y is 0.90. With rtable = 0.339 it can be concluded that rcount> rtable (0.90> 0.339), so it can be concluded that there is a relationship between Interest (X1), 30 Meter Running (X2) and Leg Muscle Explosive Power (X3) with Long Jump Ability (Y) of Students of SMA Negeri 1 Peulimbang in the 2012/2013 Academic Year.